(3TQM efGQ GdCfhGQs - (3eLghds
(3ChdgG (B:s
(3GdOGQjf fGQG hcGf dg TQhM bGd WhGd fjGd ef WGdYgG edGd cdGd fSCdc Cf fTQMg TQMG Ydi WQjbI GdMd eNJUQG ebGUO GdeJf MGhjG Ydi YhGFOgG GdHQjYI (B( (3cPG (B) (3NGhjG ef RhGFOgG NGhjG ef RhGFOgG GdHTjYI hYdi dWGFa aQGjO LjOI hLOjOIs
(3BNQgG (B:s
(3dCf MQeI GdfaS ahb MQeI GdeGd aLGR Cf jLYd GdeGd hbGjI ddfaS aEPG GSJhaGg Vefg dHbGA YUeJg hdgPG (B( ) (3aj gPjf GdbSejf hgeG GdKGdK hGdQGHY MJi UGQ TgjOG dGfg jchf HGPdG faSg dEYRGR Ojf Gddg JYGdi hdEbGeIMb GdTQYs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3CUhd Gdabgs